1989
DOI: 10.1007/bf00149377
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial cisplatin for the treatment of malignant gliomas

Abstract: Cisplatin (DDP) is a chemotherapeutic agent that has shown efficacy against primary CNS malignancies. Intra-arterial (IA) administration of DDP to patients with brain tumors should produce higher peak levels of drug than intravenous (IV) administration of an identical dose and reduce systemic toxicity. Twelve patients with malignant glioma were entered into the study. All had failed irradiation, 11 had failed IA BCNU. Each patient received IA DDP, 58-100 mg/m2, into the internal carotid artery at four to six w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Most recent studies of cisplatin therapy for gliomas have been based on the ia route of administration [9,[12][13][14][15]. Our results for partial responses and stabilization are comparable to those from studies based on ia cisplatin (Table 2).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Most recent studies of cisplatin therapy for gliomas have been based on the ia route of administration [9,[12][13][14][15]. Our results for partial responses and stabilization are comparable to those from studies based on ia cisplatin (Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…Since then the bulk of the clinical trials of this drug have concentrated on intra-arterial administration as part of primary therapy [2,3]. Although intraarterial (ia) therapy has the advantage of increasing the time concentration integral exposure of tumor to drug [4], there are two chief disadvantages to this route of administration, namely, (a) only a minority of malignant gliomas reside within a single carotid territory [5,6] and (b) toxicity in the eye [7,8] and brain [9]. Because of these disadvantages of ia cisplatin and because cisplatin demonstrates less cross resistance in vitro with chloroethylnitrosoureas than other drugs in gliomas [10], we evaluated iv cisplatin for treatment of recurrent malignant gliomas at higher dosage than previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Brain toxicity due to cisplatin or BCNU has been suggested to be a function of cumulative dose [8,21]. Our data would indicate that time is also a factor in the occurrence of brain toxicity.…”
Section: Discussionmentioning
confidence: 55%
“…Historically, intra-arterial CDDP has been tested alone or in combination with other drugs for the treatment of primary or recurrent gliomas. Several trials combining BCNU and IA CDDP have been reported with survival times ranging from 8 weeks to 48 months for responders [17][18][19][20][21]. CDDP intraarterially has also been associated with bleomycin [22], BCNU and VM-26 [23], and etoposide [24].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand Calvo et al [25], Newton et al [21], and Mortimer et al [14] reported no significant ototoxicity in the combined 51 patients diagnosed with malignant gliomas they treated with IA CDDR Recht et al [11] reported only a 7 % rate of ototoxicity utilizing IA CDDP with intravenous BCNU. This is even more remarkable when it is taken into consideration that the doses of CDDP exceed those utilized in this report.…”
Section: Discussionmentioning
confidence: 99%